**E**l e c t ro nic
**J**

o f

**P**r

ob a bi l i t y

Electron. J. Probab.**18**(2013), no. 88, 1–33.

ISSN:1083-6489 DOI:10.1214/EJP.v18-2513

**Stationary product measures for conservative particle** **systems and ergodicity criteria**

### Richard Kraaij

^{∗}

**Abstract**

We study conservative particle systems on W^{S}, where S is countable and W =
{0, . . . , N}orW =N, where the generator reads

Lf(η) =X

x,y

p(x, y)b(ηx, ηy)(f(η−δx+δy)−f(η)).

Under assumptions onband the assumption thatpis finite range, which allow for the exclusion, zero range and misanthrope processes, we determine exactly what the stationary product measures are.

Furthermore, under the condition thatp+p^{∗},p^{∗}(x, y) :=p(y, x), is irreducible, we
show that a stationary measureµis ergodic if and only if the tail sigma algebra of
the partial sums is trivial underµ. This is a consequence of a more general result on
interacting particle systems that shows that a stationary measure is ergodic if and
only if the sigma algebra of sets invariant under the transformations of the process
is trivial. We apply this result combined with a coupling argument to the stationary
product measures to determine which product measures are ergodic. For the case
thatW is finite, this gives a complete characterisation.

In the case thatW =N, it holds for nearly all functionsbthat a stationary product measure is ergodic if and only if it is supported by configurations with an infinite amount of particles. We show that this picture is not complete. We give an example of a system wherebis such that there is a stationary product measure which is not ergodic, even though it concentrates on configurations with an infinite number of particles.

**Keywords:** Exclusion process; zero-range process; misanthrope process, stationary product
measures, ergodic measures, coupling.

**AMS MSC 2010:**Primary 60G10; 60K35; 82C22, Secondary 60G50.

Submitted to EJP on December 23, 2012, final version accepted on September 21, 2013.

SupersedesarXiv:1212.1302.

∗Delft Institute of Applied Mathematics, Technical University Delft, the Netherlands.

E-mail:r.c.kraaij@tudelft.nl

**1** **Introduction**

For the exclusion, inclusion, zero range, and misanthrope process [12, 5, 3, 7] there
is a long history of research into the stationary and ergodic measures. For the exclusion
process, it is known for a long time that the model has invariant product measures which
are indexed by the particle density per site. It was shown that the model has stationary
measures which have a constant density and that there are measures which are indexed
with some parameter(λx)_{x∈S}, P[ηx= 1] = _{1+λ}^{λ}^{x}

x, that is reversible with respect to the random walk kernelp, i.e. λxp(x, y) =λyp(y, x), see e.g. [12].

A similar picture was shown to be true for other models as well [5, 7]. For the zero range process, however, this picture was not complete as was shown by Andjel [3].

The underlying parametersλfor a product measure in case of the zero range process were only required to satisfy P

xλ_{x}p(x, y) = λ_{y}. In 2005, Bramson and Liggett [4]

extended the picture for the exclusion process by showing that product measures for
which(λx)_{x∈S} satisfiesP

xλxp(x, y) =λy and ifλxp(x, y)6=λyp(y, x), thenλx=λy, are stationary as well.

The problem of findingall ergodic measuresfor such systems is still open. Progress has been made to classify which stationary product measures are ergodic. For the exclusion process, this problem was solved in Jung [10]. For the zero range process, the problem was solved by Sethuraman [17] under some additional conditions on the interaction functiong. Similar issues have been studied for the misanthrope process and the inclusion process [2, 7]. For different models, different methods are being used. Sethuraman [17], however, uses an approach that works for a range of models.

In this paper, we show that these questions can dealt with regardless of the spe- cific model, i.e. we will work with systems with a generator of the form Lf(η) = P

x,yp(x, y)b(η_{x}, η_{y})(f(η−δ_{x}+δ_{y})−f(η)) wherepis finite range and where function
b depends on the model that we are working with. We will takebbounded for conve-
nience, but the methods are not restricted to this case.

We start in section 2 by proving that a stationary measureµis ergodic if and only if the tail sigma algebra of the partial sums is trivial underµ. In fact, this is a consequence of a result that is valid for more general interacting particle systems(IPS). We will show that a stationary measureµfor a general IPS is ergodic if and only if the sigma algebra of sets that are invariant under the possible transformations of the system is trivial under µ. This result also shows that stationary measures for Glauber dynamics are ergodic if and only if they are tail trivial.

In section 3, we will address the question of stationarity of product measures. We show that the idea of Bramson and Liggett [4] extends to other models and that the structure of the set of stationary invariant measures depends crucially on the structure of the functionb.

After that, we apply these results in section 4 to show which product measures are ergodic. We use a coupling proof to extend the results of Jung [10] to the case where W ={0, . . . , N}, which completely resolves the question ifW is finite. We use the same techniques to show similar results for the case that W = N. In this case however, we find interesting behaviour. For most functions b, we see that a product measure is ergodic if it has zero mass on configurations with a finite number of particles. This behaviour is consistent with the behaviour found for the zero range process [17]. For certain functionsb, however, this behaviour breaks down, as we illustrate in section

5 with an example of a system where we have a stationary, but non ergodic, product measure which concentrates on configurations with an infinite amount of particles, but which follows a certain increasing deterministic profile.

**1.1** **Main Results**

LetE=W^{S} be the set of configurations(η_{x})_{x∈S} for a countable setW and a count-
able set S. Let B be the product σ-algebra. For example, the exclusion process is
defined on {0,1}^{S}, the zero range process on N^{S}, and the stochastic Ising model on
{−1,1}^{S}. Byη(t) = (η(t))_{i∈S} we describe the configuration of the process at timet. We
orderS by a bijection φ : S → N^{, so}i < j ifφ(i) < φ(j). Using this ordering, define
S_{n}={x∈S : φ(x)≤n}andBn=σ{ηi : i∈S_{n}}. Define

∆f(i) := sup{|f(η)−f(ζ)| : forj6=i: ηj=ζj} the variation off ati∈S. Define the space of test functions by

D:=

(

f ∈C_{b}(E) : |||f|||:=X

x∈S

∆_{f}(x)<∞
)

. (1.1)

Defineη^{x,y} =η−δx+δy and let∇x,yf(η) =f(η^{x,y})−f(η)Forf ∈D, we define
L^{b,p}f(η) :=X

x,y

p(x, y)b(η_{x}, η_{y})∇x,yf(η).

Note that forW ={0,1}andb(n, k) =n(1−k)we obtain the exclusion process and that
forW = N^{and} b(n, k) = g(n)we obtain the zero range process. We will refer to bas
the rate function and to this class of processes by the nameproduct type processes. We
will assume that

**Assumption 1.1.** pis finite range and
sup

x

X

y

(p(x, y) +p(y, x)) =:C_{p}<∞.

We also make the following assumption. Denote withp^{∗}(x, y) :=p(y, x).

**Assumption 1.2.** p+p^{∗}is irreducible andbis positive except for the two casesb(0,·) = 0
and ifW ={0, . . . , N}:b(·, N) = 0.

In the case thatW is a finite set, we know by theorem I.3.9 in Liggett[12] that there
exists a process η(t) and semigroup St : C(E) → C(E)corresponding to L^{b,p}. With
the same techniques it is not hard to show that there is a processη(t)and semigroup
S_{t} : D → D in the case that W = N^{and} b is bounded. In both cases D is a core for
L^{b,p}. Note that in the case thatW =Nit is not the case thatD=C(E). It seems that
Dwhich is the uniform closure of bounded local functions is the natural space to work
with.

The zero range process has been constructed also for unboundedbin Andjel [3], the results that we obtain in this article do not improve upon the results of Sethuraman [17]

with respect to the zero range process, so we will not deal with with this construction.

The methods developed here apply to the zero range process as the methods are valid regardless of the structure ofb.

For a more general interacting particle system, we follow the notation of Liggett
[12]. ForT a finite subset ofSandζ ∈W^{T} letcT(η, ζ)be the rate at which the system

makes a transformation from configurationη to configurationθ_{T ,ζ}(η)which is defined
by

θT ,ζ(η)i:=

(ηi ifi /∈T
ζ_{i} ifi∈T
and putc_{T} := sup{c_{T}(η, W^{T}) : η∈E}. Lastly, define

∇T ,ζf(η) :=f(θT ,ζ(η))−f(η).

For functionsf ∈D, defineLby puttingLf to be Lf(η) :=X

T

Z

c_{T}(η,dζ)∇_{T ,ζ}f(η). (1.2)
If we assume W to be finite, theorem I.3.9 in Liggett [12] gives that L generates a
Markov processη(t)and semigroupSt:C(E)→C(E)for whichDis a core.

**Assumption 1.3.** For general interacting particle systems, we work under the condi-
tions of theorem I.3.9 in Liggett [12]. In particular we assume that

sup

x

X

T3x

cT =C <∞. (1.3)

We have stated assumption (1.3) as it is needed for the proof of proposition 2.2. Note that in the particular case of product type systems, assumption 1.1 implies assumption 1.3.

Furthermore, we define the set of stationary measures for the process generated by LbyI(L). Proposition 4.9.2 in Ethier and Kurtz [6] shows that

I(L) =

µ : Z

Lfdµ= 0 ∀f ∈D

. (1.4)

We start with stating the result on ergodicity.

**1.2** **Ergodic measures for general IPS**

In this section, we work with a generatorLthat is given by equation (1.2). For the results that follow, we need the following assumption.

**Assumption 1.4.** Forη∈E,T ⊂Sa finite set,ζ∈W^{T} such thatc_{T}(η, ζ)>0there is a
n∈N, there are finite setsT1, . . . , Tn⊂Sandζ1∈W^{T}^{1}, . . . , ζn ∈W^{T}^{n} such that for all
i≤n:

cT_{i} θTi−1,ζi−1◦ · · · ◦θT_{1},ζ_{1}◦θT ,ζ(η), ζi

>0 and

θTn,ζn◦ · · · ◦θT1,ζ1◦θT ,ζ(η) =η

This assumptions states that if the Markov process allows the transformation fromη toθT ,ζ(η), then there is a sequence of possible transformations that returns the config- uration toη. Under this assumption, we can define the followingσ-algebra.

**Definition 1.5.** For a generatorL, define theσ-algebra GL of sets that are invariant
under transformations of the process generated byL. That means that ifG∈ G_{L} and
η∈G,T ⊂Sfinite,ζ∈W^{T} such thatc_{T}(η, ζ)>0thenθ_{T ,ζ}(η)∈G.

Note that by assumption 1.4,GL is aσ-algebra. We now state the main theorem of this section.

**Theorem 1.6.** IfLgenerates a Markov process andµ∈ I(L), thenµis ergodic if and
only ifG_{L}is trivial underµ.

We give two corollaries to this theorem regarding two examples, see corollary 1.11 below. The first class of examples are spin flip systems, with a generators that read

Lf(η) =X

x

r(x, η)(f(η^{x})−f(η))

for some rate function r, where W = {−1,1} and η^{x}_{y} = ηy if y 6= x and η_{x}^{x} = −ηx.
Important examples are stochastic Ising models.

The second class of examples are conservative systems, of which the product type systems are a special case. The generator is given by

Lf(η) =X

x,y

r(x, y, η)∇x,yf(η).

Also Kawasaki dynamics belongs to this case.

Under some small assumptions, we identify theσalgebraGL for these two types of systems.

**Definition 1.7.** Define the followingσ-algebras.

(a) The tailσ-algebra:

T :=\

n

σ (ηx : x∈Ssuch thatφ(x)≥n).

(b) The tailσ-algebra of the partial sums:

H:=\

n

Hn :=\

n

σ

X

φ(x)≤m

η_{x} : m > n

.

(c) A, theσ-algebra of events that are invariant under moving particles from one site to
another. In other words,Ais the collection of setsAsuch that ifη∈Aandx, y∈S,
such thatη_{x}>0, and in the case thatW ={0, . . . , N},η_{y}< N, then alsoη^{x,y}∈A.
First, we show that the last twoσ-algebras are equal.

**Lemma 1.8.** It holds thatA=H.

We use this information combined with the following irreducibility assumptions to obtain corollary 1.11.

**Assumption 1.9.** In the case that we are working with a conservative particle sys-
tem, we assume thatc is irreducible. This means that if we have two configurationsη
and ηˆsuch that there is a finite box B ⊂ S such that η agrees with ηˆoutside B and
P

x∈Bηx=P

x∈Bηˆx, then there exists a sequence of configurationsη0=η, . . . , ηn = ˆη,
so that we have a sequence of sites inS:x0, . . . xn such thatηi=η^{x}_{i−1}^{i−1}^{,x}^{i} and jump rate
r(xi−1, xi, ηi−1)>0.

Consider for example a product type conservative particle system, then this assump-
tion is satisfied ifpis irreducible and bis positive except for the two cases b(0,·) = 0
and ifW ={0, . . . , N}: b(·, N) = 0. It is easy to see that this assumption implies that
G_{L}b,p=A=H.

**Assumption 1.10.** In the case that we are working with a spin flip system, we assume
that

infx,ηr(x, η)>0

Under this assumption, we see that GL = T. In fact, we have this equality under weaker assumptions onr, but we do not consider this here, as this result will not be used for the rest of the paper.

**Corollary 1.11.** (a) If L generates a spin flip system and µ ∈ I(L), then GL = T.
Hence,µis ergodic if and only ifT is trivial underµ.

(b) If L generates a conservative particle system and µ ∈ I(L) then GL = A = H. Hence,µis ergodic if and only ifHis trivial underµ.

**Remark 1.12.** (b) holds under condition 1.9. In the case that we are working with a
product type system, irreducibility ofcis implied by the irreducibility of p. We would
like to obtain this result for stationary product measures under the condition thatp+p^{∗}
is irreducible, i.e. condition 1.2. In corollary 1.19, we will show that this relaxation is
possible.

The use of theorem 1.6 is not restricted to these cases however. For example it can
also be applied to the tagged particle process [13, 16, 15]. These models are just like
the product type IPS, but now one is interested in the properties of a single particle, the
tagged particle. One starts the dynamics from a translation invariant stationary product
measure. Important information can be obtained by looking at the environment as seen
from this tagged particle: the environment process. It is proven that the environment
process also has a stationary product measure, see e.g. [13], proposition III.4.3, or
[16], proposition 7. One would like to prove that this measure is ergodic, see [13],
proposition III.4.8. The results in this paper give with minor adaptations a shorter
proof of this proposition. First of all a stationary measureν is ergodic if and only if
A ∩ I is trivial under ν, where I is the σ-algebra of shift invariant sets. The results
below in theorem 1.20 show under which conditionsA, henceA ∩ I, is trivial underµ.
**1.3** **Results on product measures for product type conservative particle sys-**

**tems**

We return to product type systems where the generator reads
L^{b,p}f(η) =X

x,y

p(x, y)b(η_{x}, η_{y})∇_{x,y}f(η).

For the existence of product stationary measures we make the following two assump- tions.

**Assumption 1.13.** For alli, j∈W we have
b(i+ 1, j−1)

b(j, i) = b(1, j−1) b(j,0)

b(i+ 1,0) b(1, i) .

This property ensures that we obtain a set of invariant product measures and can be traced back to Cocozza-Thivent [5]. A second assumption is needed for the caseW =N and will be explained below.

**Assumption 1.14.** IfW =Nwe assume that
infi

b(i+ 1,0)

b(1, i) =I >0.

Under these assumptions, the process generated by L^{b,p} has a natural class of in-
variant product measures. These are defined in the following way.

a0= 1 ak =

k−1

Y

i=0

b(1, i) b(i+ 1,0) Zλ=X

k

akλ^{k}
λ^{∗}= lim inf

i

b(i+ 1,0) b(1, i)

(1.5)

λ^{∗} is the radius of convergence of the formal sum Zλ, so for λ < λ^{∗}, we have that
Z_{λ} <∞. Note that if we are working withW ={0, . . . , N}, then we only definea_{k} for
k≤N and as a consequence,λ^{∗} is infinite. Because of assumption 1.14, we know that
λ^{∗}≥I > 0. This is also the reason for assumption 1.14. It can only be violated in two
ways, eitherλ^{∗}= 0, or there is ani≥1such thatb(i,0) = 0, which gives problems when
definingakfork≥i.

Extendλto have one value for each point inS, soλ∈[0, λ^{∗})^{S}.
**Definition 1.15.** Letλ∈[0, λ^{∗})^{S}. Forx∈S, define the marginal

µ_{λ}_{x}(n) =Z_{λ}^{−1}

xa_{n}λ^{n}_{x}.
The measureµ_{λ}is defined as the product measure onW^{S}:

µλ=⊗_{x∈S}µλ_{x}.
The set of measures of this type is denoted by

P⊗(b) =

µλ : λ∈[0, λ^{∗})^{S} .

We see that given a functionb, we obtain the set of measuresP⊗(b). Note however that different b’s can lead to the same set of probability measures. We identify the stationary product measures of this type.

**Proposition 1.16.** Let λbe a solution ofP

xλxp(x, y) = λyP

xp(y, x). Depending on the structure ofb, we have the following:

(a) If for all k it holds that b(n, k) = b(n,0), i.e. the zero range process, then µλ ∈
I(L^{b,p}).

(b) Ifb(n, k)−b(k, n) =b(n,0)−b(k,0) andλis such that ifλxp(x, y)6=λyp(y, x), then
λx=λy , then it holds thatµλ∈ I(L^{b,p}).

(c) Ifλ_{x}p(x, y) =λ_{y}p(y, x)for allxandythenµ_{λ}∈ I(L^{b,p}).

Furthermore, an invariant measureµ_{λ} in the setP_{⊗}(b)must be of one of these three
types, i.e. λis a solution ofP

xλ_{x}p(x, y) =λ_{y}P

xp(y, x)and the pair(λ, b)satisfies (a), (b) or (c).

**Remark 1.17.** Note that the conditionb(n, k)−b(k, n) = b(n,0)−b(k,0)is equivalent
tob(n, k) =r(n) +s(n, k)wheresis symmetric. Choose for exampler(n) =b(n,0).
**Remark 1.18.** Furthermore, it is an interesting question whether these results can be
extended to infinite rangep.

Now that we know what the class of invariant product measures is, we can apply
corollary 1.11. But first, we show that irreducibility ofpcan be relaxed to irreducibility
ofp+p^{∗}.

**Corollary 1.19.** Ifp+p^{∗}is irreducible andµ∈ I(L^{b,p})∩ P_{⊗}(b)thenµis ergodic if and
only ifHis trivial underµ.

A coupling argument is used to prove the following theorem. For a fixed generator
L^{b,p}pickµλ∈ I(L^{b,p})∩ P_{⊗}(b).

**Theorem 1.20.** SupposeW ={0, . . . , N}, thenµλ is ergodic if and only ifP

i:λi<1λi+ P

i:λ_{i}≥1
1
λ_{i} =∞.

Suppose thatW =Nand that one of the following holds.

(a) λ^{∗}<∞

(b) λ^{∗}=∞and there exists a finite setD={d1, . . . , dp}so thatgcd(D) = 1such that
D⊂

(

d≥1 : sup

k

a^{2}_{k}

a_{k−d}a_{k+d} = sup

k d−1

Y

i=0

b(k+i+ 1, k−i−1) b(k−i, k+i) <∞

) .

(c) P

i:λ_{i}<Iλi+P

i:λ_{i}≥I
1
λi =∞

Then it holds thatµλis ergodic if and only ifP

iλi=∞.

In the case thatW ={0,1} this result was proved also by Jung [10]. His condition P

x λx

(1+λx)^{2} =∞seems different but is equivalent to the one given here.

**Remark 1.21.** Condition(b)is satisfied for example if it holds thatsup_{k} ^{b(i+1,i−1)}_{b(i,i)} <∞.
**Remark 1.22.** In the case thatW =N, one might think that it is possible to prove that
P

iλ_{i}=∞implies thatµ_{λ}is ergodic, without any further conditions like (a), (b), or (c).

We show that this is not possible in section 5. We give an example of a system whereb andphave a specific structure such that there exists a product measures of the given type such thatP

iλi =∞, whileµλis not ergodic.

This raises the question under which additional assumptions P

iλi = ∞ implies ergodicity. The proof in the case that W = N shows some analogy with the proof of theorem 1.8 in Aldous and Pitman [1] and the open question we see here is similar to the open question in [1], see theorem 1.8 and example 7.5 in that article.

**Remark 1.23.** We give an explanation for the symmetric nature of theorem 1.20 in the
case thatW is a finite set. We will see that the condition for ergodicity means that the
measure concentrates on configurations which have an infinite number of particles i.e.

Pηi = ∞, but also such thatP

i(N −ηi) = ∞, i.e. infinitely many anti-particles. We
give a more intuitive view on this by the following approach. Instead of saying that a
particle moves from sitexto siteywith ratep(x, y)b(η_{x}, η_{y}), one could say that an empty
spot, or anti-particle moves from siteyto sitexwith ratep(y, x)˜˜ b(N−η_{y}, N−η_{x}), where

˜b(n, k) =b(N−k, N−n),

˜

p(x, y) =p(y, x).

For more details on this rewrite, see section 6 below.

**2** **Proof of theorem 1.6 and lemma 1.8**

We start with the proof of lemma 1.8, which states thatA=H. We refer to the point
φ^{−1}(0)as the origin.

Proof of lemma 1.8. LetA∈ Aand fixn, we show thatA∈ H_{n}. By the defining property
of A, we see that A does not depend on the exact configuration of η in Sn given its
configuration on S_{n}^{c}, but just on the sum of the values in Sn. We elaborate on this
argument a little for the case that W = N. If one understands the argument for this
case then it is clear for the finite case too. Suppose that we have a configurationη∈A.
We see that the configurationη(n)_{i} = (P

j∈Snη_{j})δ_{φ}−1(0)(i) +P

j /∈Snη_{i}δ_{j}(i)is inA too,
becauseA ∈ A. So any configuration that is equal to η outsideSn and has P

i∈Snηi

of particles inSn is inA. This means that given the configuration outsideSn, 1^{A}^{only}
depends on thisP

i∈Snηi. HenceA∈ Hn, butnwas arbitrary, soA∈ H.

LetA∈ H. Pick aη∈A, we show that forxandyso thatη_{x}>0thatη^{x,y}∈A. Pick a
nso thatn > φ(x), φ(y). We know thatA∈ HnsoAdoes not depend on the exact values
inSnbut only on the sumP

i∈Snηiwhich is not changed by moving a particle fromxto
y, thereforeη^{x,y} ∈A. This yieldsA∈ A.

We start with proving theorem 1.6, but for this we need some machinery. Fix a measureµ∈ I(L).

**Proposition 2.1.** The semigroupSt onD extends to a semigroupS_{t}^{µ} onL2(µ). This
in turn defines a unbounded operatorL^{µ}, with domainD(L^{µ})which is the closureLin
L2(µ). Dis also a core forL^{µ}.

We denote the norm onL2(µ)by||·||_{µ}. The proof is rather standard, but we give it for
sake of completeness in our general setting.

Proof. By invariance ofµ, we obtain that

||Stf||^{2}_{µ} ≤ ||f||^{2}_{µ}.

Hence, we see thatS_{t}viewed as a operator on the subset D ⊂ L2(µ)is a contraction.

We now prove thatDis dense inL_{2}(µ). Clearly,Dcontains all local bounded functions,
which implies that its closure inL2(µ)contains all local functions inL2(µ). We prove
that all local bounded functions inL2(µ)are dense inL2(µ).

Recall the definitions ofB_{n}. Pick a boundedf ∈ L_{2}(µ)and define the local functions
fn = E[f | Bn]. As taking a conditional expectation is a projection in a L2 space, we
see that||fn||_{µ}≤ ||f||_{µ}. Furthermore, the sequencefnis a martingale with respect to the
filtration(Bn)_{n≥0}. By martingale convergence,fnconverges tof inL2(µ).

By a truncation argument, we see that the bounded functions are dense inL2(µ), so indeedDis dense inL2(µ).

So, St, being a contraction with respect to the Hilbert space norm onD ⊂ L2(µ),
defines by a continuous extension a linear operator S_{t}^{µ} on L2(µ). This also defines a
generatorL^{µ}with domain

D(L^{µ}) :=

f ∈ L2(µ) : lim

t↓0

S_{t}^{µ}f−f

t ^{exists in}L2(µ)

.

As we clearly have that||·||_{µ} ≤ ||·||_{∞}, it holds thatL^{µ} is the closure ofLandD ⊂ D(L^{µ}).
AsDis a core forL, we obtain thatDis a core forL^{µ} as well.

This last statement is obtained by using proposition 3.1 from Ethier and Kurtz [6].

This proposition shows thatR(λ−L)is dense inDfor someλ >0. We know thatDis
dense inL2(µ), henceR(λ−L^{µ})is dense inL2(µ). The same proposition yields thatD
is a core forL^{µ}.

We now give a technical result which helps us to analyse the structure of the setI. Define in the spirit of lemma IV.4.3 of Liggett [12] and Sethuraman [17] the following two quadratic forms, forf for which they are finite:

Q(f) =−E^{µ}[f L^{µ}f]
R(f) =1

2 X

T

Eµ

Z

c_{T}(η,dζ)(∇T ,ζf(η))^{2}

Liggett defines bilinear forms instead of quadratic ones, we will not do that here because the following result is only true for quadratic forms. Below we will show that equality for bilinear forms is possible only in the case that the underlying measureµis reversible with respect to the dynamics.

**Proposition 2.2.** Forf ∈ D(L^{µ}):

Q(f) =R(f)<∞

Proof. The proof is analogous to that of lemma IV.4.3 in Liggett [12]. We will not repeat the proof here, the key step that is different is to note that forf ∈Dit holds that

E^{µ}[f L^{µ}f] =E^{µ}[f L^{µ}f]−1

2E^{µ}[L^{µ}f^{2}].

After that simply work out the right hand side and plug in the arguments from [12].

The same techniques can be used to prove that forf, g∈ D(L^{µ})

−E^{µ}[f L^{µ}g+gL^{µ}f] =X

T

E^{µ}
Z

cT(η,dζ)(∇T ,ζf(η))(∇T ,ζg(η))

by using thatE^{µ}[f L^{µ}g+gL^{µ}f] =E^{µ}[f L^{µ}g+gL^{µ}f−L^{µ}(f g)]. This shows that we have
equality for bilinear forms only whenµis reversible with respect to the dynamics.

For the proof of theorem 1.6, we introduce approximating Markov processes. Recall the definition ofSn. Define forf ∈D

L^{(n)}f(η) = X

T⊂Sn

Z

c_{T}(η,dζ)(f(θ_{T ,ζ}(η))−f(η)).

Because S_{n} is a finite set, L^{(n)} is a bounded operator which therefore generates a
Markov Jump process with semigroupS_{t}(n). This semigroup also extends to S_{t}^{µ}(n)on
L2(µ).

Proof of theorem 1.6. Suppose thatµis ergodic. Pick a setA ∈ G_{L}, we need to show
that µ(A) ∈ {0,1} or equivalently that the function 1A is constant µ almost surely.

Intuitively one would like to say thatL^{µ}1^{A}= 0, because clearly for everyη, finiteT ⊂S
andζ∈W^{T} it holds that∇T ,ζ1^{A}(η) = 0, henceS_{t}^{µ}1^{A}=1^{A}^{for all}t, hence by ergodicity
1^{A}is constantµalmost surely.

This reasoning is not rigorous, as we do not know whether1A∈ D(L^{µ}). However, by
corollary I.3.14 in Liggett [12] we obtain thatS_{t}^{µ}(n)f →S_{t}^{µ}ffor allf ∈ L_{2}(µ), uniformly
fortin compact intervals.

The set A ∈ GL is invariant under finitely many transformations of the form η to
θ_{T ,ζ}(η)forT andζ so thatc_{T}(η, ζ)>0. Denote the Markov process generated byL^{(n)}
byη_{n}(t). Under the law of this Markov process, the set on which there are only a finite
number of allowed transitions by timethas probability1. This means that for any start-
ing configurationη,t ≥0 andn∈N it holds thatS_{t}^{µ}(n)1^{A}(η) =E^{η}[1^{A}(ηn(t))] =1^{A}(η).
Hence, for everytandnit holds thatS_{t}^{µ}(n)1^{A} =1^{A}in the spaceL2(µ). Furthermore,
S_{t}^{µ}(n)1^{A}→S_{t}^{µ}1^{A}, implying thatS_{t}^{µ}1^{A}=1^{A}^{in}L2(µ)for everyt.

Now we can use the ergodicity of µ with respect to the Markov process to obtain that 1A isµ constant almost surely, which implies thatµ(A) ∈ {0,1}. SinceA ∈ GL is arbitrary, we see thatGL is trivial underµ.

For the second implication assume thatG_{L}is trivial underµ. FixA∈ Band assume
thatS_{t}^{µ}1^{A}=1^{A}µa.s. for allt≥0. We will show that there is a setA_{∞}∈ GLsuch that
µ(A) =µ(A_{∞}). First note that1^{A}∈ D(L^{µ})andL^{µ}1^{A}= 0. Hence, by proposition 2.2 we
see thatR(f) = 0. This in turn implies that the setB0defined by

η : ∃T ⊂S finite, ζ∈W^{T}, such thatcT(η, ζ)>0,1^{A}(η)6=1^{A}(θT ,ζ(η))

hasµmeasure zero. LetA0 =A. DefineA1 =A0\B0 and note that1^{A}0 =1^{A}1 µa.s.

becauseµ(B0) = 0. This means that

S_{t}^{µ}1^{A}1 =S_{t}^{µ}1^{A}0 =1^{A}0 =1^{A}1 µa.s.

This yields that the setB1defined by

η : ∃T ⊂S finite, ζ ∈W^{T}, such thatcT(η, ζ)>0,1^{A}1(η)6=1^{A}1(θT ,ζ(η))

has measure0. DefineA2=A1\B1. We can repeat this step and constructA3,A4,. . ..
Note thatAn+1 ⊂An andµ(An+1) =µ(An)for alln. DefineA_{∞}=T

nAnand note that µ(A∞) =µ(A).

We show that A_{∞} ∈ G_{L}. Suppose η ∈ A_{∞}, T ⊂ S finite and ζ ∈ W^{S} such that
cT(η, ζ) > 0, we must prove that θT ,ζ(η) ∈ A_{∞}. This is not to difficult, suppose that
θT ,ζ(η)∈/ A_{∞}, then there is aN >0so that for alln≥N θT ,ζ(η)∈/ An, but then for all
n > N η /∈An, so that it follows thatη /∈Awhich is a contradiction.

This means thatµ(A) =µ(A_{∞})∈ {0,1}, because of triviality ofG_{L}underµ.

**3** **Proof of corollary 1.19 and proposition 1.16**

First, we give a consequence of the definition of the product measures inP⊗(b). Let Abe the set defined by

A=

({ηy >0} ∩ {ηx< N} ifW ={0, . . . , N} {ηy >0} ifW =N.

On the set A, defineµ^{y,x}_{λ} to be the measure obtained from µλ by the transformation
η7→η^{y,x}, i.e. 1^{A}µ^{y,x}_{λ} (dη) =1^{A}µλ(dη^{y,x}).

**Lemma 3.1.** For µ_{λ}, the Radon-Nikodym derivative corresponding to the change of
variablesη^{y,x}toηis given by

1^{A}dµ^{y,x}_{λ}

dµ_{λ} (η) = b(ηy, ηx)
b(η_{x}+ 1, η_{y}−1)

λx

λ_{y}.

Proof. The transformationη7→η^{y,x}only affects two coordinates. Hence,
1^{A}dµ^{y,x}_{λ}

dµλ

(η) =1^{A}aη_{x}+1

aη_{x}

aη_{y}−1

aη_{y}

λx

λy

= b(1, η_{x})
b(ηx+ 1,0)

b(η_{y},0)
b(1, ηy−1)

λ_{x}
λy

= b(η_{y}, η_{x})
b(ηx+ 1, ηy−1)

λ_{x}
λy

. In the last line we use assumption 1.13.

Using this information, we take a look at proposition 2.2 and theorem 1.6 in the case
thatµ=µ_{λ}, a stationary product measure.

**Corollary 3.2.** Forµλa stationary product measure, it follows that

−Eµλ

f L^{b,p}f

=1 2

X

x,y

Eµλ

"

p(x, y) +_{λ}^{λ}^{y}

xp^{∗}(x, y)

2 b(η_{x}, η_{y}) (∇_{x,y}f(η))^{2}

# .

Furthermore, ifµ_{λ}a stationary product measure forL^{b,p}, thenµ_{λ}is ergodic if and only
ifG_{L}b,(p+p∗)is trivial underµ_{λ}.

This strengthening is useful, because the fact thatp+p^{∗}is irreducible implies that
H=G_{L}b,(p+p∗), which effectively proves corollary 1.19.

Proof. By proposition 2.2, we know that

−E^{µ}λ

f L^{b,p}f

=1 2

X

x,y

E^{µ}λ

h

p(x, y)b(ηx, ηy) (∇x,yf(η))^{2}i
.

Pickx, y∈S, then we obtain by lemma 3.1 that Eµλ

hp(x, y)b(η_{x}, η_{y}) (∇x,yf(η))^{2}i

= Z

p(x, y)b(η_{x}, η_{y}) (f(η^{x,y})−f(η))^{2}µ_{λ}(dη)

= Z

p(x, y)b(η^{y,x}_{x} , η^{y,x}_{y} ) (f(η)−f(η^{y,x}))^{2}µ^{y,x}_{λ} (dη)

= Z

p(x, y)λx

λ_{y}b(ηy, ηx) (f(η^{y,x})−f(η))^{2}µλ(dη)

=E^{µ}λ

p(x, y)λx

λ_{y}b(ηy, ηx) (∇y,xf(η))^{2}

.

This implies that 1 2

X

x,y

Eµλ

hp(x, y)b(η_{x}, η_{y}) (∇x,yf(η))^{2}i

=1 2

X

x,y

E^{µ}λ

p(x, y)

2 b(ηx, ηy) (∇x,yf(η))^{2}

+X

x,y

E^{µ}λ

"

p(x, y)^{λ}_{λ}^{x}

y

2 b(ηy, ηx) (∇y,xf(η))^{2}

#

=1 2

X

x,y

E^{µ}λ

"

p(x, y) +^{λ}_{λ}^{y}

xp^{∗}(x, y)

2 b(ηx, ηy) (∇x,yf(η))^{2}

# .

This equality implies that we can redo the proof of theorem 1.6 by usingG_{L}b,(p+p∗) in-
stead ofG_{L}b,p to obtain thatµ_{λ}is ergodic if and only ifG_{L}b,(p+p∗) is trivial underµ_{λ}.

Define the relationx∼ y ifλxp(x, y) =λyp(y, x). We start the proof of proposition 1.16 with:

**Lemma 3.3.** Letλ:S→R^{+}be a solution ofP

xλxp(x, y) =P

xλyp(y, x)and suppose that ifλxp(x, y)6=λyp(y, x), thenλx=λy. Then it holds that

X

xy

p(x, y) =X

xy

p(y, x).

Proof. This is a short calculation.

X

x

λyp(y, x) =X

x

λxp(x, y)

=X

x∼y

λxp(x, y) +X

xy

λxp(x, y)

=X

x∼y

λ_{y}p(y, x) +X

xy

λ_{y}p(x, y)

Proof of proposition 1.16. FixL^{b,p}and pick a measureµλ∈ P_{⊗}(b).

Letf ∈D. We are allowed to rearrange the terms in the next calculation, becausef is a local function andpis finite range.

Z

Lfdµλ= Z X

x,y

p(x, y)b(ηx, ηy)(f(η^{x,y})−f(η))µλ(dη)

= Z X

x,y

p(x, y)b(η^{y,x}_{x} , η^{y,x}_{y} )f(η)µ^{y,x}_{λ} (dη)

− Z X

x,y

p(x, y)b(ηx, ηy)f(η)µλ(dη)

= Z

X

x,y

p(x, y)λx

λ_{y}b(ηy, ηx)f(η)µλ(dη)

− Z

X

x,y

p(x, y)b(ηx, ηy)f(η)µλ(dη)

= Z

f(η)X

x,y

b(η_{x}, η_{y})

p(y, x)λ_{y}
λx

−p(x, y)

µ_{λ}(dη)

(3.1)

We arrive at the fourth line by using lemma 3.1 on the first term. We obtain the last expression by changing the roles ofxandyin the first term.

Clearly, if for allx, yit holds thatx∼y then the integral is0. This is case (c). Now
suppose that this is not the case and we have a pairi, j such thatλip(i, j)6= λjp(j, i).
Then the above argument does not work. Note that if we can prove that that for all
η_{x}, η_{y}it holds thatP

x,yb(η_{x}, η_{y})[p(y, x)^{λ}_{λ}^{y}

x−p(x, y)] = 0, then we are done. We start with 1.15(b), suppose that ifxythenλx=λy.

X

x,y

b(ηx, ηy)

p(y, x)λy

λx

−p(x, y)

=X

x

X

yx

b(η_{x}, η_{y})[p(y, x)−p(x, y)]

=X

x

X

yx

b(ηx, ηy)p(y, x)−X

x

X

yx

b(ηx, ηy)p(x, y)

=X

x

X

yx

b(ηx, ηy)p(y, x)−X

y

X

xy

b(ηy, ηx)p(y, x)

=X

x

X

yx

b(η_{x}, η_{y})p(y, x)−X

x

X

yx

b(η_{y}, η_{x})p(y, x)

=X

x

X

yx

p(y, x)[b(ηx, ηy)−b(ηy, ηx)]

=X

x

X

yx

p(y, x)[b(η_{x},0)−b(η_{y},0)]

=X

x

X

yx

b(ηx,0)[p(y, x)−p(x, y)]

=X

x

b(ηx,0)X

yx

[p(y, x)−p(x, y)]

= 0

In line five we use that∼is a symmetric relation. In line seven we use the second item in the assumptions. and in line eight we switch back the way we switched forward in lines two to five. In the last line we use lemma 3.3.

For the proof of item (a), note that the method above does not work in this case as
we cannot use reversibility or the relation∼^{. However,} b(n, k) reduces tob(n,0). We
check again thatP

x,yb(η_{x}, η_{y})[p(y, x)^{λ}_{λ}^{y}

x −p(x, y)] = 0. X

x,y

b(η_{x}, η_{y})

p(y, x)λ_{y}
λx

−p(x, y)

=X

x

b(ηx,0)X

y

p(y, x)λy

λx

−p(x, y)

= 0

The last equality is due to the primary assumption onλ:P

xλxp(x, y) =λyP

xp(y, x).
We now prove that an invariant measure in the set P_{⊗}(b) must be of one of the
three given types. Pick a point z ∈ S and a finite set B(z) containing z such that if
x /∈ B(z), thenp(z, x) = p(x, z) = 0, i.e. B(z)contains all points that can be reached
by p from z. Let F(z) = {η : ifx ∈ B(z)\ {z}thenηx = 0}. Furthermore, let
F^{∗}(z) ={η : ifx∈B(z)thenηx = 0}. Note that1^{F(z)} ^{and}1^{F}^{∗}^{(z)}are local bounded

functions, hence inD. Now fix some generatorL =L^{b,p} for which we knowp, but do
not know the specific form ofb.

Suppose that we have a product measureµλ∈ P⊗(b), for a non-zeroλand suppose
thatµ_{λ} is invariant for the process generated byL^{b,p}. This yieldsR

L1F(z)dµ_{λ} = 0and
RL1F^{∗}(z)dµ_{λ}= 0by equation (1.4). We now look at these integrals. First, note that by
definition of our indicator function we only have to look at couples where xory is in
B(z). The third equality is due to a calculation similar to the one in equation (3.1).

0 = Z

L1F(z)dµλ

=

Z X

xory∈B(z)

b(η_{x}, η_{y})p(x, y) 1F(z)(η^{x,y})−1F(z)(η)
µ_{λ}(dη)

= Z

1F(z)(η) X

y∈B(z)

b(η_{z},0)

p(y, z)λ_{y}
λz

−p(z, y)

µ_{λ}(dη)

+ Z

1F(z)(η) X

x /∈B(z)

X

y∈B(z)

b(ηx,0)

p(y, x)λy

λx

−p(x, y)

µλ(dη)

(3.2)

When using the same methods on the function1^{F}^{∗}^{(z)}µλ(ηz= 0)^{−1}, we obtain
0 =µ_{λ}(η_{z}= 0)^{−1}

Z

L1F^{∗}(z)dµ_{λ}

=µλ(ηz= 0)^{−1}
Z

1F^{∗}(z)(η) X

x /∈B(z)

X

y∈B(z)

b(ηx,0)

p(y, x)λy

λ_{x}−p(x, y)

µλ(dη)

We know thatµλ is a product measure and in the last line the only term involving the
integral over ηz is the function1^{F}^{∗}^{(z)}, but clearly 1^{F}^{∗}^{(z)} = 1^{F(z)}1{ηz=0}. Hence, we
can first integrate overη_{z} such that the normalising term disappears and then add the
integral overη_{z}, because it integrates to1:

0 =µλ(ηz= 0)^{−1}
Z

1F^{∗}(z)(η) X

x /∈B(z)

X

y∈B(z)

b(ηx,0)

p(y, x)λy

λ_{x}−p(x, y)

µλ(dη)

= Z

1F(z)(η) X

x /∈B(z)

X

y∈B(z)

b(η_{x},0)

p(y, x)λ_{y}
λx

−p(x, y)

µ_{λ}(dη)

(3.3)

Combining (3.2) and (3.3), we obtain that 0 =

Z

1F(z)(η) X

y∈B(z)

b(ηz,0)

p(y, z)λy

λz

−p(z, y)

µλ(dη) (3.4)

After integrating overηz, we obtain that P

y

h

p(y, z)^{λ}_{λ}^{y}

z −p(z, y)i

= 0. Hence,λsolves P

yλ_{y}p(y, z) =λ_{z}P

yp(z, y).

For the subdivision into items (a), (b), and (c), we adapt the above argument by look- ing at two sites. Pick two distinct sitesz andwsuch thatp(z, w)orp(w, z)is non-zero.

Fix a finite setB(z, w)⊂S containing zand wsuch that ify /∈B(z, w), then p(z, y) =
p(y, z) = p(w, y) = p(w, y) = 0. Let F(z, w) ={η : ifx ∈ B(z, w)\ {z, w}thenηx =
0, ηz =n, ηw=k}and letF^{∗}(z, w) ={η : ifx∈B(z, w)thenηx= 0}. We do a similar
calculation.

0 = Z

L1F(z,w)dµ_{λ}

= Z

1F(z,w)(η)b(ηz, ηw)

p(w, z)λw

λz

−p(z, w)

µλ(dη) +

Z

1^{F(z,w)}(η) X

y∈B(z,w)\{w}

b(ηz, ηy)

p(y, z)λy

λz

−p(z, y)

µλ(dη)

+ Z

1F(z,w)(η)b(ηw, ηz)

p(z, w)λz

λ_{w} −p(w, z)

µλ(dη) +

Z

1F(z,w)(η) X

y∈B(z,w)\{z}

b(ηw, ηy)

p(y, w)λy

λw

−p(w, y)

µλ(dη)

+ Z

1F(z,w)(η) X

x /∈B(z,w)

X

y∈B(z,w)

b(ηw, ηy)

p(y, w)λy

λ_{x}−p(x, y)

µλ(dη)

We clarify the last expression. We have split the sum overx and y into a number of parts, in the first two linesx=z, in the second two linesx=wand in the last line we sum overx /∈B(z, w). The sum overx∈B(z, w)\ {z, w}does not play a role because on the setF(z, w)we integrate overb(0,·) = 0. The term in the last line is 0because it is equal to

µλ(ηz=n) µλ(ηz= 0)

µλ(ηw=k) µλ(ηw= 0) Z

L1F^{∗}(z,w)dµλ,

just like in the argument where we singled out only one point inS. We obtain that 0 = X

y6=w

b(n,0)

p(y, z)λy

λ_{z} −p(z, y)

+X

y6=z

b(k,0)

p(y, w)λ_{y}
λw

−p(w, y)

+b(n, k)

p(w, z)λ_{w}
λz

−p(z, w)

+b(k, n)

p(z, w)λ_{z}
λw

−p(w, z)

.

Now, we add the terms missing from the first two sums and subtract them from the last two sums:

0 =b(n,0)X

y

p(y, z)λ_{y}
λz

−p(z, y)

+b(k,0)X

y

p(y, w)λy

λw

−p(w, y)

+ [b(n, k)−b(n,0)]

p(w, z)λw

λ_{z} −p(z, w)

+ [b(k, n)−b(k,0)]

p(z, w)λz

λ_{w} −p(w, z)

Note that the first 2 lines are zero, becauseλsatisfies X

x

λ_{x}p(x, y) =X

x

λ_{y}p(y, x).

Therefore, we obtain

0 = [b(n, k)−b(n,0)]

p(w, z)λ_{w}
λz

−p(z, w)

+ [b(k, n)−b(k,0)]

p(z, w)λ_{z}
λw

−p(w, z)

.

(3.5)

From equation (3.5), we can derive necessary conditions for λ to yield an invariant measure for a certainb.

Suppose thatbdoes not depend on the second variable,b(n, k) =b(n,0), then we see that this yields0 in equation (3.5). This is option (a) in the proposition. Now suppose that we have akso thatb(n, k)6=b(n,0). We can rewrite equation (3.5) as the following equality:

[b(n, k)−b(n,0)]

p(w, z)λw

λ_{z} −p(z, w)

= λz

λw

[b(k, n)−b(k,0)]

p(w, z)λw

λz

−p(z, w)

This gives by the assumption thatp(z, w) +p(w, z)>0either b(n, k)−b(n,0) = λz

λw

[b(k, n)−b(k,0)] (3.6)

or

p(w, z)λw

λ_{z} −p(z, w) = 0. (3.7)

Now we can simply take λ to be reversible, which is exactly equation (3.7). This is
option (c) in the proposition. Suppose that we have two siteszand wso thatλis not
reversible:p(w, z)_{λ}^{λ}^{z}

w −p(z, w)6= 0, then equation (3.6) must hold.

Consider the situation where _{λ}^{λ}^{z}

w =c6= 1, thenb(n, k)−b(n,0) =c(b(k, n)−b(k,0)).
Note that becauseb(n, k)6=b(n,0), clearlyb(k, n)6=b(k,0), so we could have made the
same argument with n and k the other way around to obtain that b(n, k)−b(n,0) =
c^{−1}(b(k, n)−b(k,0)), a contradiction. Hence the assumption thatp(w, z)^{λ}_{λ}^{w}

z −p(z, w)6= 0 leads to the fact that λz = λw. And this in turn leads by equation (3.6) to b(n, k)− b(k, n) =b(n,0)−b(k,0). This is option (b) in the proposition.

**4** **Proof of theorem 1.20**

We prove the following two theorems, which imply theorem 1.20 by using corollary
1.11. Letµ_{λ} ∈ I(L^{b,p})∩ P⊗(b), andλnot identically0. We will denoteµ_{λ} byP^{in this}
section.

**Theorem 4.1.** In the case thatW ={0, . . . , N}the following are equivalent.

1. Ais trivial.

2. P

i:λi<1P[ηi >0] +P

i:λi≥1P[ηi< N] =∞ 3. P

i:λ_{i}<1λ_{i}+P

i:λ_{i}≥1 1
λi =∞

**Remark 4.2.** In items (2) and (3), an element of the sequenceiis either in the first or
in the second sum depending on whetherλi≥1. In fact, the constant1is arbitrary and
can be replaced by any otherc >0.

In the case thatW = N there is no maximum number of particles, so we need to adjust (2) and (3).

**Theorem 4.3.** Suppose thatW =N, and that one of the following assumptions holds.

(a) λ^{∗}<∞

(b) λ^{∗}=∞and there exists a finite setD={d1, . . . , dp}so thatgcd(D) = 1such that

D⊂ (

d≥1 : sup

k

a^{2}_{k}

a_{k−d}a_{k+d} = sup

k d−1

Y

i=0

b(k+i+ 1, k−i−1) b(k−i, k+i) <∞

) .

(c) P

i:λ_{i}<Iλ_{i}+P

i:λ_{i}≥I 1
λi =∞

Then, we have the following equivalence.

1. Ais trivial.

2. P

iP[ηi>0] =∞. 3. P

iλi=∞.

We cut the proofs of both theorems up in three parts. Note that we only need the extra assumptions in theorem 4.3 to prove the implication (2) to (1). We start with showing the equivalence of (2) and (3).

Proof of the equivalence of (2) and (3) in theorems 4.1 and 4.3.

For the case thatW ={0, . . . , N}, we obtain by elementary calculations using the defi- nition of the measureP=µλthat

1 Z1

X

i:λ_{i}<1

λ_{i}≤ X

i:λ_{i}<1

P[η_{i}>0]≤ X

i:λ_{i}<1

λ_{i},
and

aN−1

PN k=0ak

X

i:λi≥1

1 λi

≤ X

i:λi≥1

P[ηi< N]≤ PN−1

k=0 a_{k}
aN

X

i:λi≥1

1 λi

.

In the situation whereW =N, the situation is slightly more difficult. First, use the fact thatZλ≥Z0= 1to obtain

X

i

P[ηi>0]≤X

i

P[ηi= 1]

=X

i

λi

Z_{λ}_{i}

≤X

i

λi.

For a bound in the other direction, we use the fact that assumption 1.14 implies that ak

a_{k+1} = b(k+ 1,0)

b(1, k) ≥I >0.

Using this lower bound, we find X

i

P[η_{i}>0] =X

i

∞

X

k=0

P[η_{i}=k+ 1]

=X

i

∞

X

k=0

a_{k}
ak+1

λ_{i}P[η_{i}=k]

≥IX

i

λ_{i}

∞

X

k=0

P[η_{i} =k]

=IX

i

λi.

Proof that (1) implies (2) in theorems 4.1 and 4.3.

We start with theorem 4.3 and argue by contradiction. Suppose thatP

iP[η_{i}>0]<∞,
then by Borel-Cantelli it follows that

P

"

X

i

ηi<∞

#

= 1.

Define for everyn∈ N^{the set}An ={η : P

iηi=n}and note thatAn ∈ A. It follows
by (1), that for everynit holds thatP[An]∈ {0,1}. Therefore, there is a n^{∗} such that
P[An^{∗}] = 1. Clearly, we must have thatP[An^{∗}+1] = 0. Fix some sites∈S and consider
the setA_{n}^{∗} as the disjoint union over sets that specify the number of particles ats.

1 =P[A_{n}^{∗}] =

n^{∗}

X

k=0

P

X

i6=s

η_{i}=n^{∗}−k

P[η_{s}=k]

The same approach for the setAn^{∗}+1yields
0 =P[An^{∗}+1]≥

n^{∗}

X

k=0

P

X

i6=s

ηi=n^{∗}−k

P[ηs=k+ 1]

=

n^{∗}

X

k=0

P

X

i6=s

ηi=n^{∗}−k

P[ηs=k]λs

a_{k+1}
ak

.

However, the term on the right is clearly unequal to0asλs
a_{k+1}

a_{k} >0for everyk, which
contradictsP[An^{∗}+1] = 0.

A similar approach can be used for proving (1) to (2) of theorem 4.1 by considering the set

η : X

i:λi<1

ηi− X

i:λi≥1

(N−ηi)<∞

.

The proof of (3) to (1) in both theorems uses a coupling argument.

From lemma 1.8, we know thatA=H, so we look atHinstead. AsS is a countable set, we assume for the moment that it is equal toNto simplify the notation. Define the partial sumsZn=Pn

i=0ηi, thenHis the tailσ-algebra of theZn.